2016
DOI: 10.1016/j.fss.2015.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Multilingual generation of uncertain temporal expressions from data: A study of a possibilistic formalism and its consistency with human subjective evaluations

Abstract: In NLG systems, temporal uncertainty in raw data can hamper the inference of temporal and causal relationships between events and thus impact the quality of the generated texts. In this paper, we introduce a framework to represent and reason with temporal uncertainty based on possibility theory and propose a model that uses the outcomes of such temporal reasoning to select linguistic expressions to convey uncertainty to the reader. Our model is based on Fuzzy Temporal Constraint Networks (FTCN) and our work is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Many techniques have been described to handle fuzzy spatial relationships, and we believe that reg would benefit from an exploration of this literature. Some related work has shown that fuzzy sets can be useful in generating appropriate natural language descriptions of uncertain temporal relations between events [48]; applying similar strategies to spatial relations is a promising way forward.…”
Section: Spatial Relationsmentioning
confidence: 99%
“…Many techniques have been described to handle fuzzy spatial relationships, and we believe that reg would benefit from an exploration of this literature. Some related work has shown that fuzzy sets can be useful in generating appropriate natural language descriptions of uncertain temporal relations between events [48]; applying similar strategies to spatial relations is a promising way forward.…”
Section: Spatial Relationsmentioning
confidence: 99%
“…Alternatively, automatically learn such definitions (for instance, as it is done in TSK rule-based systems [19]). • Perform experiments to obtain empirical definitions from experts or human users [14], [20].…”
Section: Distinct Approachesmentioning
confidence: 99%
“…In other cases experiments were run in order to study how human subjects use linguistic expressions in different domains (e.g. [14], [20]).…”
Section: Distinct Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several lines of research aiming to address this problem. For example, previous work has focused on addressing uncertainty in time-series data [17] and temporal uncertainty [29]. Our study addresses uncertainty derived from unknown first-time users.…”
Section: Related Workmentioning
confidence: 99%